2021
DOI: 10.3389/fmed.2021.758311
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between ER Stress, Autophagy and Inflammation

Abstract: The endoplasmic reticulum (ER) is not only responsible for protein synthesis and folding but also plays a critical role in sensing cellular stress and maintaining cellular homeostasis. Upon sensing the accumulation of unfolded proteins due to perturbation in protein synthesis or folding, specific intracellular signaling pathways are activated, which are collectively termed as unfolded protein response (UPR). UPR expands the capacity of the protein folding machinery, decreases protein synthesis and enhances ER-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 93 publications
0
48
0
Order By: Relevance
“…ER stress is a consequence of systemic inflammation ( Iwakoshi et al, 2003 ; Chipurupalli et al, 2021 ). ER stress leads to the activation of stress sensor proteins such as IRE1α, ATF6, and PERK, along with increased expression of UPR-related genes, such as GRP78 and CHOP ( Hosoi and Ozawa, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…ER stress is a consequence of systemic inflammation ( Iwakoshi et al, 2003 ; Chipurupalli et al, 2021 ). ER stress leads to the activation of stress sensor proteins such as IRE1α, ATF6, and PERK, along with increased expression of UPR-related genes, such as GRP78 and CHOP ( Hosoi and Ozawa, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…ER stress-induced UPR signaling mediates inflammation via NF-κB. All three branches of the UPR activate NF-κB via gene transcription ( Hasnain et al, 2012 ; Chipurupalli et al, 2021 ). Under normal conditions, NF-κB forms a complex with inhibitor kappa B (ΙκΒ) and is unable to translocate to the nucleus and activate gene transcription.…”
Section: Er Stress and Inflammationmentioning
confidence: 99%
“…Initially, IRE1 branch is activated when the chaperone BiP that is usually bound to the three factors, IRE1, ATF6, and PERK, disengages due to the accumulation of misfolded proteins in the ER. This leads to the autophosphorylation of IRE1 and binding to adaptor protein, TRAF2, activating JNK/AKT pathways ( Hasnain et al, 2012 ; Chipurupalli et al, 2021 ). The IRE1/TRAF2 complex also activates ΙκΒ kinase, which phosphorylates IκB, leading to NF-κB nuclear translocation and cytokine expression.…”
Section: Er Stress and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of the UPR in the pathogenesis of different myopathies such as Sporadic inclusion body myositis, Myasthenia gravis, Duchenne muscular dystrophy has been reviewed recently ( 137 ). In immune cells, ER stress and the UPR are implicated in the regulation of the inflammatory state ( 138 ). A couple of studies demonstrated that also in myocytes, proinflammatory stimuli regulate UPR signaling.…”
Section: Protein Quality Control Endoplasmic Reticulum Stress and The...mentioning
confidence: 99%